Rapid and receptor-free Prussian blue electrochemical sensor for the detection of pathogenic bacteria in blood - Ramasamy, Sriramprabha; Madhu, Sekar; Choi, Jungil (Bioelectrochemistry, 2025)
Bloodstream bacterial infections, a major health concern due to rising sepsis rates, require prompt, cost-effective diagnostics. Conventional methods, like CO2-based transduction, face challenges such as volatile metabolites, delayed gas-phase signaling, and the need for additional instruments, whereas electrochemical sensors provide rapid, sensitive, and efficient real-time detection. In this study, we developed a bioreceptor-free Prussian blue (PB) sensor platform for real-time bacterial growth monitoring in blood culture. PB thin films were electrodeposited onto a screen-printed carbon electrode (SPCE) via cyclic voltammetry (CV) technique under optimal conditions. The electrochemical performance of PB/SPCE was assessed using differential pulse voltammetry (DPV) against exoelectrogenic bacteria, including E. coli, P. aeruginosa, S. aureus, and E. faecalis. The proposed sensor exhibited surface-controlled electrochemical kinetics and bacteria-driven metal reduction from PB to Prussian white (PW), facilitated by extracellular electron transfer (EET). It showed significant sensitivity with an extensive detection range of 102–108 CFU/mL for E. coli and S. aureus, and 103–108 CFU/mL for P. aeruginosa and E. faecalis, with reliable detection limits. The sensor accessed the viability of the pathogen within 3 hrs, offering a rapid, efficient alternative to traditional, labor-intensive methods for blood-based diagnostics.
Keywords: Bacteria detection; Bacteria growth monitoring; Bacterium growth; Blood-based diagnose; E. coli; Electrochemicals; Growth monitoring; P.aeruginosa; Prussian blue; Screen-printed carbon electrodes; Bacteria; Biosensing Techniques; Electrochemical Techniques; Electrodes; Ferrocyanides; Humans; Limit of Detection; Bacteria detection; Bacteria growth monitoring; Blood-based diagnosis; Electrochemical sensor; Prussian blue